SPECIES AND FUNCTIONAL DIVERSITY OF RHIZOBACTERIA OF RICE PLANT IN THE COASTAL SOILS OF INDONESIA - Dwi Ningsih Susilowati; I Made Sudiana; N.R. Mubarik; A. Suwanto (Indonesian Journal of Agricultural Science, 2015)
Rhizobacteria are important components of soil and directly or indirectly influence the soils quality and plant growth for maintaining adequate plant nutrition and reducing the negative environmental effects of fertilizers. Applying high dose of chemical fertilizers in most of rice fields in the coastal areas could reduce the quality of the soil in the long time. There are few studies addressed to verify the species and functional diversity of cultivable rhizobacteria associated with rice plant in the coastal soils. The objective of the study was to verify the species and functional diversity of rhizobacteria isolated from the coastal soils of two rice production areas of Subang and Indramayu, West Java. Special focus was given to verify phosphate solubilization, nitrogen fixation, IAA and cellulase production of the selected 78 strains of rice rhizobacteria isolated from the coastal paddy field, as well as taxonomical analyses based on 16S rRNA. The results showed that among 78 bacterial isolates from the coastal paddy field, mostly were belonging to the Firmicutes, most of them affiliated with genera Bacillus, 75 strains produced IAA, 32 strains fixed nitrogen, 37 strains solubilized phosphate and 33 strains produced cellulase. Several strains of the rhizobacteria were capable of producing plant growth promoting substances (PGPR), alone or in combination, such as IAA, fixing nitrogen,  solubilizing phosphate, and producing cellulase. Taking all of these diverse PGPR characteristics into account, it is clear that the 78 identified isolates have great potential for improving saline soils of the coastal paddy fields in Indonesia.